Myanmar Country Environmental Analysis : A Road towards Sustainability, Peace, and Prosperity -- Synthesis Report - World Bank (World Bank, Washington, DC, 2019)
Myanmar is rich in natural resources and is a global biodiversity hotspot. Myanmar's forests and fishing industry are two significant contributors to the economy, and yet these sectors are also potentially under threat from over exploitation and mismanagement. The management of solid waste, air pollution, and the use of plastics provides another growing challenge. In addition, the role of government and other stakeholders in the management of these sectors and issues is central to whether the government will succeed in reversing the current trends and be able to find a long-term sustainable solution to the problem. This report explores the issues and challenges faced and the legal and institutional context. Through a lens of poverty reduction, social inclusion and participation, and economic growth, the report tells a story of an urgent need for institutional support and reform, improvements in the enforcement against illegal extraction of resources, behavior change in all relevant stakeholders, institutional capacity building, increased funding, and improvements in data collection and analysis. If these recommendations are acted on, then Myanmar can reverse the negative trends and lead its environment on a path toward a more sustainable future.